Grinding metre scale mirror segments for the E-ELT ground based telescope - Comley, Paul; Morantz, Paul; Shore, Paul; Tonnellier, Xavier (Technische Rundschau, Hallwag Publishers; 1999, 2011)
The next generation of ground based telescopes require many hundreds of metre scale off-axis mirrors. In this paper the grinding of a 1.45m scale Zerodur® mirror segment for the European Extremely Large Telescope (E-ELT) is introduced. Employing an R-theta grinding mode with a multi stage grinding process material removal rates of up to 187.5mm3/s are achieved, whilst typically removing up to 1mm depth of material in total. Results show a RMS form error of <1μm, with subsurface damage <10μm, and a production cycle time under 2